Pushing and pulling motion generation for humanoid robots using whole-body momentum control based on analytical inverse kinematics. (16th November 2020) - Hakamata, Yuya; Tsuichihara, Satoki; Garcia Ricardez, Gustavo Alfonso; Takamatsu, Jun; Ogasawara, Tsukasa
Abstract : As robotics technology advances, we expect humanoid robots to do strenuous work on our behalf. In everyday life, we frequently perform object manipulations. In particular, pushing and pulling motions are commonly done. Therefore, it is important to enable humanoid robots to perform these types of motions. Several studies on opening a door using a humanoid robot have been conducted. However, due to the delays of waiting for sensor data, the generated motions are slower than human motions. To speed up these motions, we propose two methods. One is to use prior knowledge of a predefined reaction force and to expand a preview control to handle the predefined force. The other is to accelerate the control of the total body momentum using analytical (not iterative) inverse kinematics. We verify the effectiveness of the proposed method in both simulation and the real humanoid robot HRP-4. GRAPHICAL ABSTRACT: UF0001